Analysis of the content of the mathematics textbook for seventh grade students in the Syrian Arab Republic in light of mathematical proficiency (Journal of Hama University, 2024)
The study aimed to analyze the content of the mathematics textbook for seventh grade students in the Syrian Arab Republic in light of the components of mathematical prowess. To achieve the goal of the study, the researcher built a list of the components of mathematical proficiency, which consisted of five components (Conceptual comprehension, procedural fluency, strategic competence, adaptive reasoning, productive desire), and a content analysis form in light of the first four components only because the fourth component is related to the learner, as it expresses the learner’s positive attitude about learning mathematics. The research sample consisted of the mathematics textbook for seventh grade students in the Syrian Arab Republic for the academic year 2023/2024, The study reached the following results:Conceptual comprehension came in first place with a frequency of (238) and a percentage of (40.07%), and procedural fluency came in second place, with a frequency of (166) and a percentage of (27.95%), while strategic competence was repeated (108) and a percentage of (18.18%), adaptive reasoning came in fourth place with a frequency of (82) and a percentage of (13.8%). In light of the previous results, a set of suggestions were